Hubungan Potensi Karir dengan Minat Menjadi Guru pada Mahasiswa Fakultas Ilmu Pendidikan - Faizia Syahralivia; Shahira Afini Azzahra; Isti Rafa Marshanda; Nabila Husna Simatupang; Ika Nadia; Fanny Zaskia Ramadhani (CV. Eracita Grup, 2026)
Career development is a dynamic process shaped by individuals’ ability to recognize their strengths, plan future goals, and prepare for occupational demands. In teacher education, students’ career potential plays a critical role in fostering interest in pursuing the teaching profession. This study aimed to investigate the relationship between career potential and interest in becoming a teacher among students of the Faculty of Education at Medan State University. A quantitative approach with a descriptive correlational design was employed. The participants consisted of 49 students selected through purposive sampling. Data were collected using Likert-scale questionnaires assessing career potential and interest in becoming a teacher and were analyzed using descriptive statistics and Pearson correlation analysis. The findings indicated that the data were normally distributed and revealed a significant positive relationship between career potential and interest in becoming a teacher, with a correlation coefficient of 0.552 and a significance level of p < 0.001. These results suggest that stronger career potential is associated with greater interest in choosing teaching as a future profession. Accordingly, strengthening career development through structured career guidance and meaningful learning experiences is essential for preparing competent and professional future teachers